Transcranial Electromagnetic Treatment “Rebalances” Blood and Brain Cytokine Levels in Alzheimer’s Patients: A New Mechanism for Reversal of Their Cognitive Impairment - Cao, Chuanhai; Abulaban, Haitham; Baranowski, Rob; Wang, Yanhong; Bai, Yun; Lin, Xiaoyang; Shen, Ning; Zhang, Xiaolin; Arendash, Gary W. (Frontiers in Aging Neuroscience, 2022)
BACKGROUND: The immune system plays a critical role in the development and progression of Alzheimer’s Disease (AD). However, there is disagreement as to whether development/ progression of AD involves an over-activation or an under-activation of the immune system. In either scenario, the immune system’s cytokine levels are abnormal in AD and in need of rebalancing. We have recently published a pilot clinical trial [https://clinicaltrials.gov/ct2/ show/NCT02958930] showing that two months of daily in-home Transcranial Electromagnetic Treatment (TEMT) was completely safe and resulted in reversal of AD cognitive impairment. METHODS: For the eight mild/moderate AD subjects in this published work, the present study sought to determine if their TEMT administration had immunologic effects on blood or CSF levels of 12 cytokines. Subjects were given daily in-home TEMT for two months by their caregivers, utilizing first-in-class MemorEMTM devices. RESULTS: For 8 plasma cytokines, AD subjects with lower baseline cytokine levels always showed increases in those cytokines after both a single treatment or after 2-months of daily TEMT. By contrast, those AD subjects with higher baseline cytokine levels in plasma showed treatment-induced decreases in plasma cytokines at both time points. Thus, a gravitation to reported normal plasma cytokine levels (i.e., a “rebalancing”) occurred with both acute and long-term TEMT. In the CSF, TEMT-induced a similar rebalancing for seven measurable cytokines, the direction and extent of changes in individual subjects also being linked to their baseline CSF levels. CONCLUSION: Our results strongly suggest that daily TEMT to AD subjects for 2-months can “rebalance” levels for 11 of 12 cytokines in blood and/or brain, which is associated with reversal of their cognitive impairment. TEMT is likely to be providing these immunoregulatory effects by affecting cytokine secretion from: 1) blood cells traveling through the head’s vasculature, and 2) the brain’s microglia/astrocytes, choroid plexus, or neurons. This rebalancing of so many cytokines, and in both brain and systemic compartments, appears to be a remarkable new mechanism of TEMT action that may contribute substantially to it’s potential to prevent, stop, or reverse AD and other diseases of aging.